Development and validation of a questionnaire measuring teaching faculties motivation from medical and medical allied universities in Myanmar - Wai, Tin Lay; Maung, Chaw Su; Lwin, Swe Mar Myint (International Journal Of Community Medicine And Public Health, 2024)
Background: Motivation status of teaching faculties in medical field can influence the students’ academic achievement, therefore, developing the tools to measure of it is essential. The study was conducted to develop and validate the questionnaire that can assess the motivation status of teaching faculties from medical and allied universities. Methods: An exploratory sequential mixed-methods study was used. The qualitative part developed a questionnaire by two rounds of Delphi expert panels. The quantitative part validated the questionnaire using both exploratory (EFA) and confirmatory factor analysis (CFA). Purposive sampling method was used for Delphi and total (661) participants for quantitative portion was selected randomly from medical and allied universities. First, 78-item questionnaire was generated based on Maslow’s hierarchy of needs theory model. Two expert panels ensured the questionnaire’s content validity and finally, developed a 68-item questionnaire. Factor analysis was conducted to validate the questionnaire with separate samples for EFA (n=331) and CFA (n=330). Results: EFA supported the four factors structure with 35 high loading items and which extracted 54% of the variance. Cronbach’s alpha coefficient and reliability values received (more than 0.7) for all constructs. The CFA further confirmed the construct, convergent and discriminant validity of the questionnaire measuring motivation status with RMSEA=0.059, CFI=0.924, TLI=0.914, SRMR=0.057. Conclusions: The final question set consisted of 35 items; communication (11 items), support (11 items), self-actualizations (9 items) and basic needs (4 items) which was shown to be a reliable and valid tool to be measure the motivation status among teaching faculties from medical and allied universities in Myanmar.